217k views
0 votes
Elimination using multiplication What is the best answer? 2x+y=0

5x+3y=2

User Dynex
by
5.1k points

2 Answers

3 votes

Answer:

x = -2, y = 4

Explanation:

2x + y = 0

5x + 3y = 2

Multiply the top equation by -3 so that one variable can be eliminated:

-3(2x + y = 0)

5x + 3y = 2

Simplify the top equation:

-6x - 3y = 0

5x + 3y = 2

Add the equations:

-x = 2

Solve for x:

x = -2

Substitute x back into one of the equations:

5(-2) + 3y = 2

Solve for y:

-10 + 3y = 2

3y = 12

y = 4

User Yupi
by
5.7k points
0 votes

Answer:

x=-2, y=4. (-2, 4).

Explanation:

2x+y=0

5x+3y=2

----------------

-3(2x+y)=-3(0)

5x+3y=2

-------------------

-6x-3y=0

5x+3y=2

---------------

-x=2

x=-2

2(-2)+y=0

-4+y=0

y=0-(-4)

y=0+4

y=4

User Frito
by
5.5k points